Chromosome studies of European cyprinid fishes: interspecific homology of leuciscine cytotaxonomic marker-the largest subtelocentric chromosome pair as revealed by cross-species painting - Ráb, Petr; Rábová, Marie; Pereira, Carla Sofia; Collares-Pereira, Maria João; Pelikánová, Sárka (Chromosome research, 2008)
Leuciscine cyprinids possess a nearly invariant diploid number (2n = 50) with an extremely uniform karyotype comprising of 8 pairs of metacentric, 13-15 pairs of submetacentric and 2-4 pairs of subtelocentric (st) to acrocentric (a) chromosomes. The largest pair is characteristically an st/a element-the 'leuciscine' cytotaxonomic marker. Previously, the interspecific homology of this chromosome pair could not be assessed owing to the inability to produce euchromatic or serial banding patterns. In the present study, we used laser-microdissection (15-20 copies of the marker chromosome) to construct a whole chromosome probe (WCP) from the marker chromosome of the roach Rutilus rutilus to ascertain the interspecific homology of marker chromosomes by cross-species in-situ hybridization. WCP was hybridized to chromosomes of widely distributed (Abramis brama, Alburnoides bipunctatus, Alburnus alburnus, Aspius aspius, Ballerus ballerus, B. sapa, Blicca bjoerkna, Chondrostoma nasus, Leucaspius delineatus, Leuciscus leuciscus, L. idus, R. rutilus, Scardinius erythrophthalmus, Squalius cephalus, and Vimba vimba) and Iberian endemic species (Achondrostoma oligolepis, Iberochondrostoma almacai, I. lusitanicum, Pseudochondrostoma duriense, S. alburnoides and S. pyrenaicus). Cross-species in-situ hybridization to chromosomes of Phoxinus phoxinus, a representative of leuciscine sister lineage, showed the same pattern as in all of the leuciscins. The probe consistently hybridized to the distal part of the short arm of the marker chromosome, indicating sequence homology.
Keywords: Genetic Markers; Sequence Homology, Nucleic Acid; Chromosome Painting; DNA sondy; chromozomy; Europe; Evropa; karyotypizace; mužské pohlaví; Karyotyping; Cyprinidae; DNA Probes; ženské pohlaví; zvířata; malování chromozomů; Chromosomes; Species Specificity; sekvenční homologie nukleových kyselin; druhová specificita; Female; genetické markery; Male; Animals